Victor Grant Collection, Album 5, Photograph 239 Mr. and Mrs. Rufus Whiteman
Mrs. Rufus Whiteman was Margaret Hart. Photograph at 50th wedding anniversay.
Designation 5.239 in listing stands for Album 5, Photograph 239.
From collection of photographs compiled by Victor Grant, descendant of the Maxwell / Beaubien family.
Located in Office Closet
Keywords: Whiteman, Rufus; Whiteman, Margaret Hart; Maxwell - Beaubien family; Whiteman family. -- New Mexico; Genealogy - Photographic collection